Comparison of oncological outcomes after segmental ureterectomy or radical nephroureterectomy in urothelial carcinomas of the upper urinary tract: results from a large French multicentre study - Colin, Pierre; Ouzzane, Adil; Pignot, Géraldine; Ravier, Emmanuel; Crouzet, Sébastien; Ariane, Mehdi M.; Audouin, Marie; Neuzillet, Yann; Albouy, Baptiste; Hurel, Sophie; Saint, Fabien; Guillotreau, Julien; et al. (BJU international, 2012)
Study Type – Therapy (multi‐centre retrospective cohort) Level of Evidence 2b What's known on the subject? and What does the study add? Upper urinary tract urothelial carcinomas (UUT‐UCs) are rare tumours. Because of the aggressive pattern of UC, radical nephroureterectomy (RNU) with bladder cuff removal remains the ‘gold‐standard’ treatment. However, conservative strategies, such as segmental ureterectomy (SU) or endourological management, have also been developed in patients with imperative indications. Some teams are now advocating the use of conservative management more commonly in cases of elective indications of UUT‐UCs. Due to the paucity of cases of UUT‐UC, only limited data are available on the oncological outcomes afforded by conservative management. We retrospectively investigated the oncological outcomes after SU and RNU in a large multi‐institutional database. Overall, 52 patients were treated with SU and 416 with RNU. There was no statistical difference between the RNU and SU groups for the 5‐year probability of cancer‐specific survival, recurrence‐free survival and metastasis‐free survival. The type of surgery was not a significant prognostic factor in univariate analysis. The results were the same in a subgroup analysis of only unifocal tumours of the distal ureter with a diameter of <2 cm and of low stage (≤T2). Our results suggest that oncological outcomes after conservative treatment with SU are comparable to RNU for the management of UUT‐UC in select cases. OBJECTIVE • To compare recurrence‐free survival (RFS), metastasis‐free survival (MFS) and cancer‐specific survival (CSS) after segmental ureterectomy (SU) vs radical nephroureterectomy (RNU) for urothelial carcinoma (UC) of the upper urinary tract (UUT‐UC) located in the ureter. PATIENTS AND METHODS • We performed a multi‐institutional retrospective review of patients with UUT‐UC who had undergone RNU or SU between 1995 and 2010. • Type of surgery, Tumour‐Node‐Metastasis status, tumour grade, lymphovascular invasion and positive surgical margin were tested as prognostic factors for survival. RESULTS • In all, 52 patients were treated with SU and 416 with RNU. The median (range) follow‐up was 26 (10–48) months. • The 5‐year probability of CSS, RFS and MFS for SU and RNU were 87.9% and 86.3%, respectively (P= 0.99); 37% and 47.9%, respectively (P= 0.48); 81.9% and 85.4%, respectively (P= 0.51). • In univariable analysis, type of surgery (SU vs RNU) failed to affect CSS, RFS and MFS (P= 0.94, 0.42 and 0.53, respectively). • In multivariable analyses, pT stage and pN stage achieved independent predictor status for CSS (P= 0.005 and 0.007, respectively); the positive surgical margin and pT stage were independent prognostic factors of RFS and MFS (P= 0.001, 0.04, 0.009 and 0.001, respectively). • The main limitation of the study is its retrospective design, which is due to the rarity of the disease. CONCLUSIONS • Short‐term oncological outcomes after conservative treatment with SU are comparable to RNU for the management of UUT‐UC in select cases and should be considered an option. • In every other case, RNU still represents the ‘gold standard’ for the treatment of UUT‐UC.